A profit model for spread trading with an application to energy futures - Takashi Kanamura; Svetlozar T. Rachev; Frank J. Fabozzi (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2011)
This paper proposes a profit model for spread trading by focusing on the stochastic movement of the price spread and its first hitting time probability density. The model is general in that it can be used for any financial instrument. The advantage of the model is that the profit from the trades can be easily calculated if the first hitting time probability density of the stochastic process is given. We then modify the profit model for a particular market, the energy futures market. It is shown that energy futures spreads are modeled by using a meanreverting process. Since the first hitting time probability density of a mean-reverting process is approximately known, the profit model for energy futures price spreads is given in a computable way by using the parameters of the process. Finally, we provide empirical evidence for spread trades of energy futures by employing historical prices of energy futures (WTI crude oil, heating oil, and natural gas futures) traded on the New York Mercantile Exchange. The results suggest that natural gas futures trading may be more profitable than WTI crude oil and heating oil due to its high volatility in addition to its long-term mean reversion, which offers supportive evidence of the model prediction.
urn:nbn:de:swb:90-232382
Keywords: C51; G29; Q40; 330; futures spread trading; energy futures markets; mean-reverting process; first hitting; time probability density; profit model; WTI crude oil; heating oil; natural gas